“Communiversity”: Students and community members work together for better environment - Anuar, Hazleen (Asia Research News, 2023)
“The students, together with their instructors, prepared the project by combining theoretical and practical knowledge in a simple yet effective way,” says materials engineer Professor Hazleen Anuar, one of the course instructors. “The community at Kampung Batu 10 gained skills and exposure to digital solutions, such as cloud technologies, and on recycling old materials, while also learning about the positive impact of reducing paper use on the environment.”